Characteristics, Development and Future of SDN - Yi Zheng; Yiqiang Hua; Xiaofeng He (Dianxin kexue)
Recently, following cloud computing, SDN becomes the network technology which the academic and industry most concerned about. Firstly, the origin, concept and effects to networks of SDN were introduced. Then the development of the architecture, core technologies and ecosystem chain of SDN were described. Finally, the major challenges and likely future were explored.